Experimental comparison of initial pool generation for direct-proportional length-based DNA computing - Ibrahim, Zuwairie; Muhammad, Mohd. Saufee; Tsuboi, Yusei; Ono, Osamu; Khalid, Marzuki (2007)
Previously, direct-proportional length-based DNA computing (DPLB-DNAC) for solving weighted graph problems such as the shortest path problem, has been proposed. After the initial pool generation, the initial pool is subjected to amplification, by polymerase chain reaction (PCR), and finally, the output of the computation can be visualized by gel electrophoresis. In this paper, we give more attention to the initial pool generation of DPLB-DNAC. For this purpose, two kinds of initial pool generation methods, which are hybridization/ligation and parallel overlap assembly (POA) are evaluated. We found that both of the methods can be successfully employed to generate the initial pool generation of DPLB-DNAC, as supported by results of actual experiments. However, POA is more preferable than that of hybridization-ligation in term of population size and generation time.